Public policy in the platform society - Nash, V; Bright, J; Margetts, H; Lehdonvirta, V (Wiley, 2017)
This editorial introduces the articles in our Special Issue (9:3–4) of Policy & Internet on “The Platform Society,” arising from the journal's IPP2016 conference held at the University of Oxford on September 22–23, 2016. The editorial provides an outline of existing academic research on online platforms; discusses platform labor, platform governance, and platform politics as three key research themes; and discusses the implications for public policy and future research directions.